Operation of NIST Josephson Array Voltage Standards - Hamilton, Clark A. (J Res Natl Inst Stand Technol, 1990)
This paper begins with a brief discussion of the physical principles and history of Josephson effect voltage standards. The main body of the paper deals with the practical details of the array design, cryoprobe construction, bias source requirements, adjustment of the system for optimum performance, calibration algorithms, and an assessment of error sources for the NIST-developed Josephson array standard.